Business Model for a Circular Economy based on Portuguese Offshore energy cluster - Pego, Ana Cristina (Technium Social Sciences Journal, 2021)
Recent studies on renewable energy and its links to the circular economy point to the importance of creating a business model that supports this relationship. For example, the importance of the circular economy has transformed the supply chain in industries in recent years and has stimulated new consumer needs and market supply in the last decade. Indeed, renewable energy is linked to the circular economy and its ability to promote positive externalities in the market. The development of this relationship gained importance when concepts such as ecosystems, welfare through recycling, blue economy and sustainable development were analyzed in the economy. This relationship is also linked to value creation in the economy and market performance. Therefore, the business model that emerged from this link was based on a new economic approach related to the supply capacity of the industry. In addition to this industrial challenge, renewable energy is one of the vectors of the circular economy and includes positive externalities for the economy, namely climate friendliness, welfare and industrial performance. The purpose of this paper is to show the relationship between renewable energy and circular economy and the industrial impacts in the economy. In order to analyze the renewable energy business model and its applicability to the circular economy in Portugal, the paper presents a qualitative methodology based on the analysis of Porter Diamond Model and SWOT. The results showed that there is a readiness to develop a business model for the environmental services sector of offshore energy cluster actors, based on the new European Policy for environmental and energy policies (2021-2027). The conclusion also showed that the offshore energy cluster-based environmental services business model in Portugal is linked to innovation ecosystems, a network platform, green production and public-private partnerships. A positive impact on the value chain is also expected from the use of renewable energy in the industry value chain. The study will contribute to European countries following this business model towards competitive and cooperative sectors